Global Patterns of Species Richness in Coastal Cephalopods - Rosa, Rui; Pissarra, Vasco; Borges, Francisco O.; Xavier, José; Gleadall, Ian G.; Golikov, Alexey; Bello, Giambattista; Morais, Liliane; Lishchenko, Fedor; Roura, Álvaro; Judkins, Heather; Ibáñez, Christian M.; et al. (Frontiers in Marine Science, 2019)
Within the context of global climate change and overfishing of fish stocks, there is some evidence that cephalopod populations are benefiting from this changing setting. These invertebrates show enhanced phenotypic flexibility and are found from polar regions to the tropics. Yet, the global patterns of species richness in coastal cephalopods are not known. Here, among the 370 identified-species, 164 are octopuses, 96 are cuttlefishes, 54 are bobtails and bottletails, 48 are inshore squids and 8 are pygmy squids. The most diverse ocean is the Pacific (with 213 cephalopod species), followed by the Indian (146 species) and Atlantic (95 species). The least diverse are the Southern (15 species) and the Arctic (12 species) Oceans. Endemism is higher in the Southern Ocean (87%) and lower in the Arctic (25%), which reflects the younger age and the “Atlantification” of the latter. The former is associated with an old lineage of octopuses that diverged around 33 Ma. Within the 232 ecoregions considered, the highest values of octopus and cuttlefish richness are observed in the Central Kuroshio Current ecoregion (with a total of 64 species), followed by the East China Sea (59 species). This pattern suggests dispersal in the Central Indo-Pacific (CIP) associated with the highly productive Oyashio/Kuroshio current system. In contrast, inshore squid hotspots are found within the CIP, namely in the Sunda Shelf province, which may be linked to the occurrence of an ancient intermittent biogeographic barrier: a land bridge formed during the Pleistocene which severely restricted water flow between the Pacific and Indian Oceans, thereby facilitating squid fauna differentiation. Another marked pattern is a longitudinal richness cline from the Central (CIP) towards the Eastern Indo-Pacific (EIP) realm, with central Pacific archipelagos as evolutionary dead ends. In the Atlantic Ocean, closure of the Atrato Seaway (at the Isthmus of Panama) and Straits of Gibraltar (Mediterranean Sea) are historical processes that may explain the contemporary Caribbean octopus richness and Mediterranean sepiolid endemism, respectively. Last, we discuss how the life cycles and strategies of cephalopods may allow them to adapt quickly to future climate change and extend the borealization of their distribution.